mHealth-Based Health Promotion Intervention to Improve Use of Maternity Care Services Among Women in Rural Southwestern Uganda: Iterative Development Study - Atukunda, Esther Cathyln; Matthews, Lynn T; Musiimenta, Angella; Mugyenyi, Godfrey Rwambuka; Mugisha, Samuel; Ware, Norma C; Obua, Celestino; Siedner, Mark J Siedner (JMIR, 2021)
Background: Antenatal care (ANC) prevents perinatal morbidity and mortality, but use of these services in Uganda remains low and maternal mortality rates are among the highest in the world. There is growing evidence that mobile health (mHealth) approaches improve timely communication of health-related information and produce positive health behavior change as well as health outcomes. However, there are limited data to guide development of such interventions in settings where ANC attendance and uptake of skilled maternity care are low. Objective: The aim of this study is to develop a novel patient-centered mHealth intervention to encourage and support women to use maternity care services in Mbarara district, southwestern Uganda. Methods: Using an iterative development approach, we conducted formative stakeholder interviews with 30 women and 5 health care providers (HCPs) to identify preferred key ANC topics and characterize the preferred messaging intervention; developed content for SMS text messaging and audio messaging with the help of 4 medical experts based on the identified topics; designed an app prototype through partnership with an mHealth development company; and pilot-tested the prototype and sought user experiences and feedback to refine the intervention through 3 sets of iterative interviews, a focus group discussion, and 5 cognitive interviews. Qualitative data were coded and analyzed using NVivo (version 12.0; QSR International). Results: Of the 75 women who completed interviews during the development of the prototype, 39 (52%) had at least a primary education and 75 (100%) had access to a mobile phone. The formative interviews identified 20 preferred perinatal health topics, ranging from native medicine use to comorbid disorders and danger signs during pregnancy. In all, 6 additional topics were identified by the interviewed HCPs, including birth preparedness, skilled delivery, male partner’s involvement, HCP interaction, immunization, and caring for the baby. Positive audio messaging and SMS text messaging content without authoritative tones was developed as characterized by the interviewed women. The postpilot iterative interviews and focus group discussion revealed a preference for customized messaging, reflecting an individual need to be included and connected. The women preferred short, concise, clear actionable messages that guided, supported, and motivated them to keep alert and seek professional help.
mHealth-Based Health Promotion Intervention to Improve Use of Maternity Care Services Among Women in Rural Southwestern Uganda:
Keywords: mHealth app; app development; messaging; health education; health promotion; mobile phone